Vaginal Primary Malignant Melanoma: A Rare and Aggressive Tumor - Georgios Androutsopoulos; Emmanouil Terzakis; Georgia Ioannidou; Athanasios Tsamandas; Georgios Decavalas (Case Reports in Obstetrics and Gynecology)
Vaginal primary malignant melanoma is a rare and very aggressive tumor. It most commonly occurs in postmenopausal women, with a mean age of 57 years. Our patient is an 80-year-old, postmenopausal Greek woman presented with a complaint of abnormal vaginal bleeding. On gynecologic examination there was a pigmented, raised, ulcerated, and irregular lesion  cm in the upper third of anterior vaginal wall. She underwent a wide local excision of the lesion. The histopathology revealed vaginal primary malignant melanoma with ulceration and no clear surgical margins. She denied any additional surgical interventions and underwent to postoperative adjuvant radiotherapy. Follow up 5 months after initial diagnosis revealed no evidence of local recurrence or distant metastasis. The prognosis of vaginal primary malignant melanoma is very poor despite treatment modality, because most of the cases are diagnosed at advanced stage. Particularly patients with no clear surgical margins and tumor size >3 cm needed postoperative adjuvant radiotherapy.